Hemorrhagic stroke as a consequence of colorectal cancer treatment with monoclonal antibody (Research, Society and Development, 2024)
Colorectal cancer is a neoplasm that affects the gastrointestinal system and has been increasingly diagnosed in Brazil, especially in adults with a family history. It has high morbidity and mortality, causing complications, one of which is hemorrhagic stroke (hstroke). This study aimed to analyze the occurrence of hstroke in a patient with colorectal neoplasia and undergoing chemotherapy and monoclonal antibody treatment. The methodology adopted for the preparation of this work followed a descriptive and qualitative approach, a case report, with emphasis on the detailed analysis of the clinical conditions, diagnosis, and treatment of a patient hospitalized, from February 20, 2023 to March 4, 2023, in a hospital located in the city of Barreirinhas, Maranhão (MA), Brazil. This was a 42-year-old patient diagnosed with metastatic colorectal cancer, who presented seizures and epistaxis at home, and, after hospital investigation, the diagnosis of hstroke was made. The literature review showed that, although cerebrovascular complications are not the main causes of death in these patients, they are of special clinical interest, since they are not common. It was concluded that there is a need for further investigation of this type of complication in this subpopulation of patients, especially in the context of chemotherapy treatment, which can directly affect vascular function and increase the risk of hemorrhagic events.